Phylogenetic relationship of Alexandrium tamiyavanichii (Dinophyceae) to other Alexandrium species based on ribosomal RNA gene sequences - Usup, G.; Leaw, C. P.; Asmat, Ahmad; Lim, P. T. (Elsevier, 2002)
The phylogenetic relationship of the thecate PSP-toxin producing dinoflagellate Alexandrium tamiyavanichii Balech to other species of Alexandrium was studied based on nucleotide sequences of the ITS1, ITS2, 5.8S, 18S and 28S subunits of the ribosomal RNA gene. These are the first such sequences available for A. tamiyavanichii, which is one of the producers of paralytic shellfish poisoning toxins in tropical waters. Based on the nucleotide sequences of the 28S, 18S and 5.8S subunits of the rRNA gene, A. tamiyavanichii grouped together with A. tamarense, A. catenella and A. fundyense. More interestingly, A. tamiyavanichii was most closely affiliated to A. tamarense isolates from Thailand. This result reaffirmed conclusions from previous studies that, for the A. tamarense/fundyense/catenella species complex, geographical origin rather than morphology seems to determine genetic relatedness. Results of this study also suggest that A. tamiyavanichii most probably belongs to the same species complex. Ribosomal RNA gene sequences do not separate the PSP toxin producing from the non-producing species of Alexandrium.